A study of risk factors and fetomaternal outcome in patients with antepartum haemorrhage in a tertiary care centre - Chauhan, Jigisha; Gheewala, Amisha; Patel, Vishwa; Patel, Henna; Agrawal, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Antepartum haemorrhage (APH) is one of the most feared complications in obstetrics, contributing to a significant amount of maternal and perinatal morbidity and mortality in our country. An antepartum haemorrhage is defined as bleeding into or from the genital tract from 24 weeks’ gestation and onwards, before the delivery of the baby. APH complicates about 2-5% of all the pregnancies with incidence of placenta previa (PP) about 0.33% to 0.55% and incidence of abruptio placenta (AP) about 0.5-1%. The maternal complications seen in patients with APH are malpresentations, premature labour, postpartum haemorrhage (PPH), sepsis, shock and retained placenta and the various foetal complications are preterm baby, low birth weight, intrauterine death, congenital malformation and birth asphyxia. Methods: A 45 patients were included in this descriptive study and detailed history taking and clinical examination was done and the resultant maternal and neonatal outcome was noted. Results: Incidence of APH in current study was calculated to be 0.53%. Out of the 45 patients, 28 (62.3%) were diagnosed with placenta previa and 17 (37.8%) were diagnosed with abruptio placenta. All 45 patients underwent caesarean section. 3 patients (6.6%) underwent obstetric hysterectomy due to diagnosis of placenta accreta spectrum. 35 alive and 8 dead born foetuses were delivered. 40% of new borns were admitted in NICU. Conclusions: Antepartum haemorrhage is a major cause of maternal and perinatal morbidity and mortality which can be prevented by early antenatal registration, regular and frequent antenatal visits, early detection and labelling of high-risk cases, and early referral to higher centre when indicated.